COGNITIVE FUNCTION PROFILE IN OBSTRUCTIVE SLEEP APNEA PATIENTS: WHICH IS MORE LIKELY TO DEVELOP? - Wardani, Rachmawati; Afif, Zamroni (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Obstructive sleep apnea (OSA) is a condition that arises from repeated episodes of upper airway collapse and obstruction during sleep that are associated with waking events with or without oxygen desaturation. OSA can cause a decrease in cognitive function. There are several neurocognitive areas of the brain that OSA and sleep deprivation can affect differently. Objective: The aim of this study is to determine the profile of cognitive disorders in OSA patients at dr. Saiful Anwar General Hospital from 2017 to 2022. Methods: This is an observational descriptive study of the results of Polysomnography and Mini-Mental State Examination (MMSE) of patients with OSA at dr. Saiful Anwar General Hospital during the period January 2017 - April 2022. Results: Results: Among the 100 subjects of the study, there were 63 men (63%) and 37 women (37%). The age distribution was as follows: 20 individuals were under 25 years old (20%), 36 people were between 25 and 45 years old (36%), 24 people were between 46 and 60 years old (24%), and 20 people were over 60 years old (20%). 12 individuals (12%) had an elementary education, 17 individuals (17%) had a junior high school education, 36 individuals (36%) had a senior high school education, and 34 individuals (34%) had an undergraduate education, according to the most recent education subject. According to the study participants' cognitive function profiles, 93 individuals (93%) had normal cognitive function, 5 individuals (5%) had mild cognitive function impairment, 2 individuals (2%) had moderate cognitive impairment, and none of the study participants had severe cognitive impairment. Conclusion: Most cognitive function profiles were normal, and the majority of OSA patients at dr. Saiful Anwar General Hospital are men. Few people acquired mild to moderate cognitive deficits and no severe cognitive impairment was seen.